UPAYA MENINGKATKAN KEMAMPUAN GURU DALAM MENYUSUN PERANGKAT PEMBELAJARAN MELALUI SUPERVISI KLINIS DI SEKOLAH BINAAN KECAMATAN CERENTI - Yurnalis Yurnalis (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research is based on the weakness of teachers in preparing the learning tools in the school assisted byCerenti Districts researcher Kuantan Singingi. The purpose of this study is to improve the quality of learningtools created by teachers in districts Cerenti. This study used a school action research design consisting of 2cycles. Each cycle consists of 4 stages namely, planning, implementation, observation and reflection. From theresult of research, Primary School 005 Sikakak in cycle I got the percentage value of 50% after the second cycleincreased to 85%, the increase of 35 points. Primary School 006 Pesikaian, in cycle I got the percentage valueof 65% and increased to 90% in cycle II, the increase of 25 points. Primary School 008 Kompe Berangin, in thefirst cycle got a value of 75% and in the second cycle increased to 90%, an increase of 15 points. PrimarySchool 010 Tanjung Medan, in cycle I got a value of 65% and increased to 85% in cycle II, the increase of 20points. Primary School 011 Pulau Panjang, in cycle I got the percentage value of 80% and in the second cycleincreased to 95%, the increase of 15 points. From the description of the data above can be concluded that, withclinical supervision can improve the quality of learning tools made teachers in Primary School Cerenti District.